2021
DOI: 10.1101/2021.08.23.457395
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Counterbalance of Foxp3 and IDO expression at different tumor stages in aggressive breast cancer subtypes

Abstract: Foxp3 and IDO1 are known immunomodulatory molecules involved in tumor escape and could be related to tumor infiltrating lymphocytes (TILs) in the tumor microenvironment. In this study, tumoral Foxp3 and IDO1 expression in breast cancer were evaluated in relation to lymphocyte biomarkers such as CD8 and CD45R0, regulatory T cells, as well as intratumoral and stromal TILs (iTILs and sTILs, respectively). Clinical and histopathological features were also included in the analysis. Foxp3 and IDO1 were found in tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 55 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…Considering that we and others had previously shown that human and murine breast cancer (BRCA) cells express Foxp3 [ 19 , 20 , 21 , 22 ], we hypothesized that the mechanism involved in the regulation of Foxp3 expression in Tregs was similar in BRCA cells. We have also reported that Foxp3 mediates BRCA cell survival, proliferation, and IL-10 secretion, effects that are similar to those observed in Tregs [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that we and others had previously shown that human and murine breast cancer (BRCA) cells express Foxp3 [ 19 , 20 , 21 , 22 ], we hypothesized that the mechanism involved in the regulation of Foxp3 expression in Tregs was similar in BRCA cells. We have also reported that Foxp3 mediates BRCA cell survival, proliferation, and IL-10 secretion, effects that are similar to those observed in Tregs [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although Foxp3 expression within the immune system is virtually restricted to Tregs, this transcription factor has also been detected in several types of normal [ 17 , 18 ] and tumoral epithelial cells, including breast cancer (BRCA) cells [ 19 , 20 , 21 , 22 ]. FOXP3 mRNA is significantly upregulated in BRCA biopsies compared with adjacent non-neoplastic breast tissue [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%